Tracing primary sources of funding for, and patterns of authorship in, climate change research in Africa. Issue 127 (January 2022) - North, Michelle A.; Hastie, Warwick W.; Craig, Marlies H.; Slotow, Rob
Abstract: African experts remain underrepresented in global climate change work and assessments, potentially from patterns of international funding, collaborations, or funder mandates. We evaluated authorship and funding of African climate science by searching Web of Science Core Collection for studies published between database inception and 31 October 2018, identifying 12561 journal articles reporting climate research in Africa. We exported the funding information, and ranked funders by the number of publications they funded. For the ten agencies funding the most publications with at least one African author, we identified all publications (n = 214) from the top five grants, by number of publications. We examined the number and position of African authors on these, and the mandates of these ten agencies. Of the publications on Africa climate research, 58% (7232) included no African authors. Among the top ten funders of African-authored publications, the South African NRF funded predominantly South African authors, while the United Kingdom's NERC, German BMBF, and USAID, funded research involving authors from 7 to 15 African countries. Only the IDRC and CGIAR have clear mandates to develop capacity within regions being studied. Overall, African climate experts are absent from much of the foreign-funded climate change research about Africa. Funders should promote collaboration with Africans when funding work on the continent, to improve African research capacity and expertise, and bolster African climate science. Most importantly, research done without local expertise may exclude important local knowledge, not be locally relevant or applicable, or miss African based solutions of potential global importance. Highlights: African authorship of African climate science is essential. Scientific authorship builds careers and legitimacy in global scientific assessments. African insight benefits the appraisal of climate impacts and fit-for-purpose solutions. Funding mechanisms can assist or hinder building capacity and collaboration. Climate science funding and publication about Africa, by Africans, is assessed.